PERSEPSI PETANI TERHADAP KINERJA PENYULUH DALAM PENGEMBANGAN PADI ORGANIK DI KECAMATAN PAGELARAN KABUPATEN PRINGSEWU - Sari, Juwita; Nurmayasari, Indah; Yanfika, Helvi (Jurnal Ilmu-Ilmu Agribisnis, 2015)
This research aimed to analyze the farmersâ perception level on performance of extension workers in organic paddy development, the factors related to farmersâ perception on the performance, and the difference of perceptions between organic paddy farmersâ and nonorganic paddy farmersâ in performance of extension workers in organic paddy development in Pagelaran Subdistrict, Pringsewu district.Â  This research was conducted in Pagelaran Village and Gemah Ripah Village in Pagelaran subdistrict, Pringsewu District.Â  Respondents were 48 farmersâ consisting of all 24 organic paddy farmersâs and 24 nonorganic paddy farmersâ which taken randomly.Â  Data were analyzed using Rank Spearman and Mann Whitney. Result showed that farmersâ perception on extension workers performance in organic paddy development was included in medium classification. Factors with real related to farmersâ perception toward performance of extension in organic paddy development were their age, knowledge, duration as a farmer and social interactions. There was no difference between organic paddy farmersâperception and nonorganic paddy farmersâ perception toward performance of extension in organic paddy development.Â  Both organic paddy farmersâ and nonorganic paddy farmersâ gave a good enough valuation towards performance of extension in organic paddy development. Key words : extension performance, farmer perception, organic paddy